TRADITIONAL FOOD AS A CREATION INNOVATION OF BORANAN BATIK SPECIAL IN LAMONGAN EAST JAVA - RAMADHAN, ANGGA FAJAR (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
AbstractBoranan traditional food is typical of Lamongan City. Food that has been passed down from generation to generation is still busy with local people. Boranan rice is still unknown by people outside Lamongan City. In particular, this research was conducted to create a boranan batik motif as the identity of Lamongan City and to introduce the existence of this food through the art of written batik. This research is a descriptive qualitative research using Gustami's craft research method, namely the exploration stage, the design stage and the embodiment stage. The exploration stage is carried out by collecting data through literature study, observation, interviews, documentation and data recording. The design stage is carried out with sketches of batik motifs and patterns. The embodiment stage is carried out by making batik using written batik techniques and using naptol coloring. The creation of a motif with a unique character and still having the characteristic form of the original rice boran food will create a new identity from the city of Lamongan. In addition, it is also able to preserve regional culture and introduce it to the wider community.